Effective Prevention of Carotid Artery Atherosclerosis by Following this Motto for Healthy Habits: “Give Up One, Reduce Two, and Increase Three” - Wada, T.; Fujishiro, K.; Fukumoto, T.; Joki, M. (Methods of Information in Medicine, 2005)
Objectives: Lifestyle has a major influence on the development and progression of atherosclerosis. Our motto for healthy habits is “give up one, reduce two, and increase three”. The one thing that is to be given up is smoking. The two things that are to be reduced are intake of food and alcohol. The three things that are to be increased are exercise, rest and enjoyable activities. We assessed correlation between these six-health habits and plaque score indicating degree of atherosclerosis in the carotid artery.Methods: Subjects were divided into unfavorable (practicing zero to three habits) and optimal (practicing four to six habits) healthy habits groups.Results: Plaque score was significantly higher in the unfavorable group (7.6 ± 5.8) than in the optimal group (4.9 ± 4.2) (P<0.001).Conclusions: The healthy habits that significantly contributed to prevention of atherosclerosis were quitting smoking and increasing rest and enjoyable activities.
Keywords: Atherosclerosis; lifestyle; carotid artery; ultrasonic